Strength Analysis of a Freight Bogie Frame under the Defined Load Cases - Jan Dizo; Miroslav Blatnicky; Jozef Harusinec; Alfred Pavlik; Lukas Smetanka (Communications - Scientific letters of the University of Zilina, 2018)
This work presents results of strength analyses of a modified freight wagon bogie frame. It consists of two main parts. The first part is addressed to introduction of the structure of a freight wagon bogie frame. It is a modified frame structure, which reflects current requirements of modern railway transport means. The conditions for rail vehicles approval and the main load cases, which every bogie frame must meet for commissioning, are described. The next part deals with computer modelling and analyses of this bogie frame. Strength analyses were performed using the FE method and they were focused on the assessment of stresses in the frame structure. Loads definition and the method of calculation were based on valid norms and standards.